The Connection between National Culture and Organizational Culture: A Literature Review - Hassan Elsan Mansaray; Hassan Elsan Mansaray Jnr (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Although there is a major challenge for international business to successfully adapt various cultures and their influence on the everyday operations of businesses. Such aptness needs to comprehend culture, cultural variety, opinions, stereotypes and values. Culture directs the way human beings act and conduct themselves in certain situations in life. It also explicates the way people from time to time treat others or talk about others. Consequently, culture in this circumstances is understood by a distinct set of people through its ideas, values, and traditions. These are the ideas, values, aspirations and traditions formed overtime by organisations that justified them to label it as ‘organizational culture’. This study made an analysis on the dissimilarities between national culture and organizational culture and discovered that Management under no circumstances can change a national culture, it can only know and utilize it. Whereas management can construct and occasionally change an organizational culture. Therefore, national culture dissimilarities exist more in values than in practices whilst organizational culture dissimilarities exist more in practices than in values.